The Role of Pesantren in Supporting the Development of UNSIQ Programs in Central Java - Machsun, Muhammad; Gusmian, Islah; Faisol, Abdul (Tarbawiyah Jurnal Ilmiah Pendidikan, 2025)
This study aims to examine the role of pesantren (Islamic boarding schools) in supporting the institutional development of Universitas Sains Al-Qur'an (UNSIQ) Central Java, particularly in Wonosobo. Using a qualitative approach, this research analyzes the contributions of pesantren in various aspects of UNSIQ’s development, including strengthening moral values, academic integrity, and the development of programs that support practical skills for students. The findings indicate that pesantren plays a significant role in reinforcing UNSIQ’s institutional identity, particularly by instilling religious values and ethics into students' academic life. Pesantren also contributes to the development of more applied curricula through entrepreneurship and agribusiness programs, as well as community empowerment activities through various outreach initiatives. The collaboration between pesantren and UNSIQ not only enriches religious education but also shapes students' character, fostering integrity and preparing them to face the challenges of the modern world. Despite challenges related to balancing academic responsibilities with pesantren activities, this synergy has a positive impact on strengthening UNSIQ’s institutional framework and realizing the vision of a holistic Islamic-based education. This study concludes that the ongoing collaboration between pesantren and UNSIQ enhances the quality of education, both academically and morally, and further strengthens the role of pesantren as a driving force in community development.